2015
DOI: 10.1242/jcs.160556
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of polycystin-1 ciliary trafficking by motifs at its C-terminus and polycystin-2 but not cleavage at GPS site

Abstract: Failure to localize membrane proteins to the primary cilium causes a group of diseases collectively named ciliopathies. Polycystin-1 (PC1, also known as PKD1) is a large ciliary membrane protein defective in autosomal dominant polycystic kidney disease (ADPKD). Here, we developed a large set of PC1 expression constructs and identified multiple sequences, including a coiled-coil motif in the C-terminal tail of PC1, regulating full-length PC1 trafficking to the primary cilium. Ciliary trafficking of wild-type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 69 publications
4
34
0
Order By: Relevance
“…Through a systematic analysis, we have further identified multiple sequences in the PC1 C tail, including the coiled-coil domain, that are involved in the regulation of PC1 ciliary trafficking. Notably, the first identified CTS for PC1, the VxP motif at the end of PC1 C tail, is completely dispensable for full-length PC1 trafficking, although we found that it is capable of driving CD16.7 to cilia as previously described by Su et al (15). CD16.7 is a well-characterized chimeric protein consisting of the human CD16 extracellular domain and the human CD7 transmembrane domain, and is frequently used for identifying functional motifs, domains, and sequences (19,(30)(31)(32).…”
Section: The 42-residue Fragment In the Pc1 C-terminal Cytoplasmic Tasupporting
confidence: 77%
See 4 more Smart Citations
“…Through a systematic analysis, we have further identified multiple sequences in the PC1 C tail, including the coiled-coil domain, that are involved in the regulation of PC1 ciliary trafficking. Notably, the first identified CTS for PC1, the VxP motif at the end of PC1 C tail, is completely dispensable for full-length PC1 trafficking, although we found that it is capable of driving CD16.7 to cilia as previously described by Su et al (15). CD16.7 is a well-characterized chimeric protein consisting of the human CD16 extracellular domain and the human CD7 transmembrane domain, and is frequently used for identifying functional motifs, domains, and sequences (19,(30)(31)(32).…”
Section: The 42-residue Fragment In the Pc1 C-terminal Cytoplasmic Tasupporting
confidence: 77%
“…These constructs are referred to as mini-constructs in this study to distinguish them from the full-length PC1 constructs. Unlike full-length PC1, which requires PC2 to reach cilia (14,15), we found that the ciliary trafficking of chimeric PC1 proteins was independent of PC2 (Supplemental Fig. S1).…”
Section: The 42-residue Fragment In the Pc1 C-terminal Cytoplasmic Tamentioning
confidence: 90%
See 3 more Smart Citations